Mean values for homogeneous stit tessellations in 3D - Nagel, Werner (Image analysis and stereology, 2008)
Recently (Nagel and Weiss, 2005), the class of homogeneous random tessellations that are stable under the operation of iteration (STIT) was introduced. In the present paper this model is reviewed and new results for the mean values of essential geometric features of STIT tessellations in two and three dimensions are provided and proved. For the isotropic model, these mean values are compared with those ones of the Poisson-Voronoi and of the Poisson plane tessellations, respectively.
Keywords: Materiali, testiranje; Materials Testing; Podatki, interpretacija statistična; Image Processing, Computer-Assisted; Data Interpretation, Statistical; Slika, obdelava z računalnikom; materiali; vzorci; statistična analiza; stereologija